MANAJEMEN KURIKULUM PENDIDIKAN KARAKTER DI PONDOK PESANTREN MODERN - Gumriadi Tambunan; Rizki Akmalia (Jurnal Bilqolam Pendidikan Islam, 2025)
Character education carried out in pesantren Modern which requires students to live in dormitories is a solution to instill character values through parenting and transparency patterns, where the school can carry out parenting patterns throughout the day and the principal and teachers act as exemplary figures that can be traced by students while in the educational environment. This research was conducted to find out the management of character education carried out in Pesantren Modern through parenting and transparency patterns with the expectation of the output of education is students who have strong character. Management of character education through parenting and transparency patterns, instrumental input in this research in the form of foundation and school policies, the vision and mission of the school, rules and regulations that apply in schools and dormitories, Another influence that will have an impact on the character education process in Pesantren Modern is the input environment, namely parenting patterns in the family environment, culture around schools and the globalization of information.